Republic Of Belarus : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation reports that Belarus experienced strong economic growth in 2004, supported by policies aimed at raising incomes and credit, and a favorable external environment. Inflation was halved during 2004, and slowed down further to 11 percent in April 2005, aided by a balanced budget, exchange rate stability, and continued remonetization. Although the economy's current momentum is likely to result in significant growth in 2005, its long-term prospects are uncertain in the absence of wide-ranging structural reforms and a phasing out of massive quasi-fiscal activities.